Causal Factors Affecting Purchase Intention Products of Cafe Amazon on Line Man Application of Consumers in Bangkok and Its Vicinity - Pankham, Sumaman; Chuenphoklang, Pukjira (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The objectives of this research article were 1) to study and validate the consistency of a causal relationship model of purchasing intention products of Cafe Amazon on the Line Man application of consumers in Bangkok and its vicinity; and 2) to find causal factors affecting purchase intention products of Cafe Amazon on the Line Man application of consumers in Bangkok and its vicinity. The tools used in the research were online questionnaires. The sample group consisted of 403 people who had bought products from Cafe Amazon on the Line Man application and live in Bangkok and its vicinity. The statistics used in data analysis were frequency, percentage, and the structural equation model. The results of the research showed that the causal relationship model of variables consisting of 5 components, which were 1) service quality, 2) customer expectation, 3) perceived value, 4) customer satisfaction, and 5) purchase intention and model developed in accordance with empirical data. The statistics showed the Chi-square statistics goodness fit test ( 2) = 335.61, CMIN/df = 1.63, degree of freedom (df) = 206, GFI = 0.94, AGFI = 0.90, SRMR = 0.04, RMSEA = 0.04. The final predictive coefficient was 0.77, indicating that the variables in the model can explain purchase intention products of Cafe Amazon on the Line Man application by 77% and service quality, customer expectation influences purchase intention products from Cafe Amazon on the Line Man application, respectively.